Cardiopulmonary bypass increases the risk of vasoplegic syndrome after coronary artery bypass grafting in patients with dialysis-dependent chronic renal failure - Hossne Junior,Nelson Américo (2015)
Abstract Objective: Coronary artery bypass grafting is currently the best treatment for dialysis patients with multivessel coronary artery involvement. Vasoplegic syndrome of inflammatory etiology constitutes an important postoperative complication, with highly negative impact on prognosis. Considering that these patients have an intrinsic inflammatory response exacerbation, our goal was to evaluate the incidence and mortality of vasoplegic syndrome after myocardial revascularization in this group. Methods: A retrospective, single-center study of 50 consecutive and non-selected dialysis patients who underwent myocardial revascularization in a tertiary university hospital, from 2007 to 2012. The patients were divided into 2 groups, according to the use of cardiopulmonary bypass or not (off-pump coronary artery bypass). The incidence and mortality of vasoplegic syndrome were analyzed. The subgroup of vasoplegic patients was studied separately. Results: There were no preoperative demographic differences between the cardiopulmonary bypass (n=20) and off-pump coronary artery bypass (n=30) group. Intraoperative data showed a greater number of distal coronary arteries anastomosis (2.8 vs. 1.8, P<0.0001) and higher transfusion rates (65% vs. 23%, P=0.008) in the cardiopulmonary bypass group. Vasoplegia incidence was statistically higher (P=0.0124) in the cardiopulmonary bypass group (30%) compared to the off-pump coronary artery bypass group (3%). Vasoplegia mortality was 50% in the cardiopulmonary bypass group and 0% in the off-pump coronary artery bypass group. The vasoplegic subgroup analysis showed no statistically significant clinical differences. Conclusion: Cardiopulmonary bypass increased the risk for developing postoperative vasoplegic syndrome after coronary artery bypass grafting in patients with dialysis-dependent chronic renal failure.